Millennial Life Satisfaction in Terms of Syukr (Gratitude) and Sabr (Patience) - Rahmania, Farra Anisa; Rusdi, Ahmad; Sari, Endah Puspita (Universitas Muhammadiyah Surakarta, 2019)
The current research revealed if syukr and sabr have a positive significant correlation with life satisfaction. The objective of this study is to investigate the correlation between syukr, sabr and life satisfaction of millennial generation. The methodology used correlation quantitative method. The subjects in this study were 164 with age range 18-23 years. The result of this research showed a significant correlation between syukr and life satisfaction (p = 0,000; p < 0,05) with a score of correlation’s coefficient 0.996 for syukr and the score of correlation’s coefficient for sabr is 0.997. Thus, this means that syukr and sabr are positively correlated with life satisfaction of millennial generation.